UPCYCLING ACTIVITIES FOR ENVIRONMENTAL AWARENESS AND CREATIVITY AMONG PRIMARY SCHOOL PUPILS IN NIGERIA - OKODUWA, Davidson; OMOROGBE, Eseosa (Journal of Early Childhood and Primary Education, 2025)
This study examines upcycling activities for environmental awareness and creativity among primary school pupils in Nigeria. Upcycling, a process that involves creatively repurposing waste materials, offers a dual advantage of reducing waste and fostering creativity. It explores the integration of upcycling activities into the curriculum of Nigerian primary schools as an educational tool for promoting environmental sustainability and developing creativity. It highlights the environmental challenges faced by Nigeria, including inadequate waste management and growing waste accumulation and positions upcycling as a practical and cost-effective solution. Through upcycling, primary school pupils can gain hands-on experience in waste reduction, resource conservation, and innovative problem-solving. This approach not only raises awareness about environmental issues but also nurtures critical thinking, collaboration and artistic expression. The paper also addresses the challenges of implementing upcycling in Nigerian schools, such as limited resources, lack of teacher training and inconsistent waste management systems and offers useful suggestions for overcoming these barriers through partnerships, curriculum integration and localised solutions. By incorporating upcycling into primary education, Nigerian schools can empower pupils to take responsibility for their environment, inspire creative thinking and contribute to the broader goal of sustainable development. This initiative presents an opportunity to shape a generation of environmentally conscious, innovative and proactive citizens prepared to tackle the ecological challenges of the future.
Keywords: Upcycling; Environmental Awareness; Creativity; Sustainable Practices; Critical Thinking